Staphylococcus aureus induces COX-2-dependent proliferation and malignant transformation in oral keratinocytes. Issue 1 (1st January 2019) - Wang, Yuxia; Liu, Shiyu; Li, Bolei; Jiang, Yaling; Zhou, Xinxuan; Chen, Jing; Li, Mingyun; Ren, Biao; Peng, Xian; Zhou, Xuedong; Cheng, Lei
ABSTRACT: The COX-2/PGE2 axis can play roles in mediating the progression of tumor. COX-2 induction was observed in oral cancer. In our previous study, we found Staphylococcus aureus, a pathogen prevalent in oral cancer, can activate the COX-2/PGE2 pathway in human oral keratinocyte (HOK) cells. Here, we investigated the proliferation of HOK cells affected by COX-2 induction and the role of COX-2 induction in the malignant transformation of HOK cells. We found S. aureus was able to facilitate HOK cell proliferation through upregulating COX-2 expression. With the induction of COX-2, expression of oral cancer-associated genes cyclin D1 was upregulated and p16 was downregulated. Transcriptome analysis showed that the "NF−kappa B signaling pathway" and "TNF signaling pathway" had the highest enrichment of differentially expressed genes (DEGs) with COX-2 over-expression. Seven upregulated genes ( jun, tlr4, cxcl1, lif, cxcl3, tnfrsf1β, and il1β ) in these two pathways were critical for the increased proliferation of HOK cells and might be associated with COX-2. Malignant transformation of cells was evaluated by soft agar colony formation assay and S. aureus infection promoted HOK cell colony formation. These results suggest the potential of S. aureus to induce the infection-associated malignant transformation of oral epitheliums through COX-2 activation. Graphical Abstract: